Pemberdayaan Ekonomi Perempuan melalui Pendampingan Usaha Kecil Perempuan di Kota Magelang: Analisis Tinjauan Maqasid al-Shariah - Aini, Qurotul; Fitriyani, Yeny; Purwanto, Purwanto (Institut Agama Islam Negeri Parepare, 2026)
This study aims to analyze the effectiveness of women's economic empowerment through small business mentoring in Magelang City, employing the Maqasid al-Shariah framework as a comprehensive analytical lens. Despite the significant role of women in the MSME sector, they continue to face structural barriers, including managerial illiteracy, limited formal financing, and low digital adoption. Using a descriptive qualitative method, this research involved 50 female culinary entrepreneurs, local government officials, and representatives from Bank Syariah Indonesia. Data were gathered through in-depth interviews and thematic analysis. The results indicate that the mentoring program significantly enhanced wealth protection (hifz al-mal) through Islamic financing and fostered managerial trustworthiness (amanah). Digital transformation was successfully adopted as a means (wasail) toward public interest (maslahah), while community networks strengthened mutual assistance (ta’awun). Crucially, the empowerment also secured psychological well-being (hifz al-nafs) by increasing self-confidence and dignity, and protected future generations (hifz al-nasl) through improved educational investment. Although facing challenges like dual-role conflicts and the digital divide, these women emerged as agents of falah, driving inclusive and resilient local economic growth. The findings emphasize the urgency of multi-stakeholder collaboration to expand sustainable, sharia-compliant mentoring models.